Coagulase-negative staphylococci strains resistant to oxacillin isolated from neonatal blood cultures - Pereira, Valeria Cataneli; Cunha, Maria De Lourdes Ribeiro De Souza Da (Instituto Oswaldo Cruz, Ministério da Saúde, 2013)
Coagulase-negative staphylococci (CoNS) are the microorganisms most frequently isolated from clinical samples and are commonly found in neonatal blood cultures. Oxacillin is an alternative treatment of choice for CoNS infections; however, resistance to oxacillin can have a substantial impact on healthcare by adversely affecting morbidity and mortality. The objective of this study was to detect and characterise oxacillin-resistant CoNS strains in blood cultures of newborns hospitalised at the neonatal ward of the University Hospital of the Faculty of Medicine of Botucatu. One hundred CoNS strains were isolated and the mecA gene was detected in 69 of the CoNS strains, including 73.2% of Staphylococcus epidermidis strains, 85.7% of Staphylococcus haemolyticus strains, 28.6% of Staphylococcus hominis strains and 50% of Staphylococcus lugdunensis strains. Among these oxacillin-resistant CoNS strains, staphylococcal cassette chromosome mec (SCCmec) type I was identified in 24.6%, type II in 4.3%, type III in 56.5% and type IV in 14.5% of the strains. The data revealed an increase in the percentage of CoNS strains isolated from blood cultures from 1991-2009. Furthermore, a predominant SCCmec profile of the oxacillin-resistant CoNS strains isolated from neonatal intensive care units was identified with a prevalence of SCCmec types found in hospital-acquired strains.
Keywords: coagulase; negative staphylococci; mecA; SCCmec